Defeating poverty: an analysis of private health investment in rural Béguédo and Ouarégou in Burkina Faso - Sarigda, Maurice; Bacye, Yisso Fidèle; Kiemde, Adama; Badini-Kinda, Fatoumata (Budapest International Research and Critics University, 2024)
In Burkina Faso, more than three out of four private health facilities are located in urban areas, 90% of them in Ouagadougou and Bobo Dioulasso. In terms of economic profitability, a private health service is more profitable in urban than in rural areas. And yet, private health facilities have been set up in rural areas, notably in Béguédo and Ouarégou in Burkina Faso. What explains private health provision in rural areas? A qualitative method was adopted to answer this research question. As in urban areas, profitability is the driving force behind the choice of rural areas by promoters, but promoters also cite reasons other than economic ones: altruism, reciprocity, awareness of saturation and increased competition in urban areas. These logics allow us to deconstruct the macroeconomic analysis of poverty, which does not take into account the specificity of each rural locality.